Editorial of JHIA Vol. 2 (2014) Issue 1 - Korpela, Mikko (Journal of Health Informatics in Africa, 2014)
The Journal of Health Informatics in Africa (JHIA) was launched in 2013 as a major step forward for the health informatics community in Africa. Since the beginning of the HELINA (Health Informatics in Africa) series of conferences in 1993 and the later formal establishment of the HELINA association as the Africa Region of IMIA (International Medical Informatics Association), only one book of full-text edited conference proceedings had been published. Scientific papers on health informatics in Africa had been published only in general journals, mostly outside of the continent (Korpela, 2013). The HELINA association decided to take a cautious approach on starting a scientific journal of its own, to ensure the sustainability of the effort despite it being completely based on voluntary resources. At least for the first couple of years, it was decided to publish two issues per year, one of which would be the edited proceedings of a HELINA conference and the other one an open-call issue. The association decided simultaneously to start to organize the conference annually, instead of the three year intervals initially decided on in 1993. This decision made HELINA conferences more in par with other IMIA conferences (AMIA, MIE, Medinfo) but also increased significantly the stress on restricted voluntary resources. This issue starts the second volume (2014) of the JHIA. In accordance with the plan, it is an open-call issue containing of full scientific papers submitted to the journal and subjected to a double-blind peer reviewing process. Due to several unfortunate factors however, there was no public call for submissions and the editorial work on this issue started late. The editorial team thus wishes to express its gratitude to the authors – Marlen Chawani, Eustache Muteba, Aanuoluwapo Olajubu, Nima Shidende and their co-authors – for their activism for keeping JHIA on track. Well done, ladies, you have cleared the way for male researchers to follow your example in terms of both quality and initiative! A major unfortunate factor, i.e. the Ebola epidemic, forced the HELINA 2014 conference to be postponed from October 2014 to March 2015. The second issue of volume 2 of JHIA, comprising the edited proceedings of HELINA 2014, will thus be published as a late issue. This also means that there will be no HELINA 2015 conference and consecutively both issues of JHIA volume 3, 2015, will be open-call issues. Reference Korpela M. Two decades of HELINA conferences: A historical review of health informatics in Africa. IMIA Yearbook of Medical Informatics 2013: 197-205.